The Role of Social Media in Constructing Religious Moderation Discourse: an Analysis of Tiktok - Dendi Superdi (Social Impact Journal, 2025)
The transformation of religious communication in the digital era has positioned social media as a new space for disseminating religious values. TikTok, as one of the most popular platforms in Indonesia, functions not only as a source of entertainment but also as an arena for contesting religious discourse. This study aims to examine the role of TikTok in shaping the discourse of religious moderation among the younger generation. The method employed is a literature review using a thematic approach, involving analysis of various academic publications from 2020 to 2025 that are relevant to the themes of religious moderation, social media, and digital communication. The findings indicate that several TikTok content creators have successfully represented the values of moderation—such as tawasuth (moderation), tasamuh (tolerance), tawazun (balance), and i’tidal (justice)—through visual storytelling, informal language, and communication strategies that are contextual and adaptive to digital culture. Nevertheless, several challenges remain, such as the dominance of extreme religious narratives, negative audience responses, and limited digital literacy. This study concludes that TikTok holds strategic potential for disseminating messages of moderate and inclusive religiosity, provided that appropriate communication strategies are employed, digital literacy is strengthened, and collaboration is fostered among content creators, communities, and religious institutions through the establishment of a systematic and organized moderation content task force.